Multimodality imaging in thoracic aortic diseases: a clinical consensus statement from the European Association of Cardiovascular Imaging and the European Society of Cardiology working group on aorta and peripheral vascular diseases. (7th March 2023) - Evangelista, Artur; Sitges, Marta; Jondeau, Guillaume; Nijveldt, Robin; Pepi, Mauro; Cuellar, Hug; Pontone, Gianluca; Bossone, Eduardo; Groenink, Maarten; Dweck, Marc R; Roos-Hesselink, Jolien W; Mazzolai, L; et al.
Abstract: Imaging techniques play a pivotal role in the diagnosis, follow-up, and management of aortic diseases. Multimodality imaging provides complementary and essential information for this evaluation. Echocardiography, computed tomography, cardiovascular magnetic resonance, and nuclear imaging each have strengths and limitations in the assessment of the aorta. This consensus document aims to review the contribution, methodology, and indications of each technique for an adequate management of patients with thoracic aortic diseases. The abdominal aorta will be addressed elsewhere. While this document is exclusively focused on imaging, it is of most importance to highlight that regular imaging follow-up in patients with a diseased aorta is also an opportunity to check the patient's cardiovascular risk factors and particularly blood pressure control.